IMPLEMENTATION OF ARTICLE 5 OF LAW 31 OF 2014 CONCERNING THE PROTECTION OF WITNESS AND VICTIMS IN THE STATE COURT OF BANDA ACEH - Leny Oktaviyanti (Sean Institute, 2022)
Article 5 of Law Number 31 of 2014 concerning the protection of witnesses and victims regulates the rights of witnesses and victims and the author focuses more on the rights of witnesses in criminal acts of corruption, in matters of witness rights and will relate to the implementation of article 5 regarding whether or not witness protection is applied at the Banda Aceh District Court because the success of a criminal justice process depends on the evidence that has been successfully disclosed in court, especially witness testimony is an important factor so that witness protection is needed as regulated in the law. And one of the factors in the absence of application of witness protection is the difference in the testimony of witnesses of corruption in the BAP and in court. From the problems above, the problem is how to implement Article 5 of Law Number 31 of 2014 against witnesses of corruption crimes in the Banda Aceh District Court, and what are the factors causing the differences in the statements of witnesses of corruption in the BAP (Minutes of Investigation) and in court based on the judge's observations. The research method used is empirical juridical by conducting interviews, observations, and documentation. The results and conclusions of the study indicate that the protection of the rights of witnesses carried out by the Banda Aceh District Court has not been implemented as stated in Article 5 of Law Number 31 of 2014 due to many obstacles faced, starting from the authorized institution, namely the Witness Protection Agency and the Witness Protection Agency. victim (LPSK), budget or funds, and from the government. And there are differences in the statements of witnesses in the Minutes of Examination with those in Court based on research with the judge, namely there are three factors, the influence of the investigator, the influence of the defendant, and the fear of the witness.